(untitled) - De Souza Buriti, Mateus; Cézac, Pierre; Casás, Lidia (Comptes Rendus. Chimie)
Jarosite-type compounds are complex-structured minerals that are widely distributed in natural environments, utilized in industrial processes, or formed as byproducts of these processes. Consequently, a comprehensive understanding of the kinetics and thermodynamics of jarosite precipitation and dissolution is important for the effective control and management of this mineral. However, literature data is lacking or inconsistent regarding these phenomena. The availability of accurate and reliable data is of utmost importance for the development and improvement of robust hydrometallurgical processes and for regulating the environmental impact of this mineral. In light of this importance, this work aims to review the most important studies published up to 2023 related to obtaining data on jarosite dissolution and precipitation. Therefore, this article contributes to a detailed analysis of the current state of the art and outlines future prospects for research on this secondary mineral.